Global Research Trends on Preconception Care on the Infertility Prevention: A Bibliometric Study - Novika, Revi Gama Hatta; Sari, Atriany Nilam; Nurhidayati, Siti; Maulina, Rufidah; Maulida, Luluk Fajria; Wahidah, Nurul Jannatul; Ilyas, Muhana Fawwazy (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Infertility affects approximately one in six individuals globally and remains a growing reproductive health concern, often linked to modifiable risk factors present before conception. Preconception care (PCC) has gained recognition as a preventive strategy, however the implementation of PCC at scale remains challenged and yet its research landscape in relation to infertility remains under-mapped.This study aimed to analyze global research trends on preconception care in the context of infertility prevention using bibliometric methods.Subjects and Method: A bibliometric analysis was conducted using the Scopus database, with data retrieved on May 12, 2024. The search strategy included terms related to PCC and infertility, yielding 486 eligible publications after screening. Included documents were English-language publications in final form, relevant to preconception care and infertility, and classified as articles, reviews, conference papers, or book materials. Analysis was performed using Scopus tools, Biblioshiny (R), and VOSviewer to examine publication trends, key contributors, and thematic evolution.Results: A total of 486 publications from 1991 to 2025 were identified, with an annual growth rate of 6.43%. Most documents were original articles (67.7%) and reviews (28.4%), authored by 2,529 contributors across 307 publication sources. Several national strategies have formalized PCC into broader public health policy to reduce disparities in pregnancy outcomes and unmet fertility needs, but there remains a critical gap in the global PCC research agenda, such as the heterogeneity in intervention protocols.Conclusion: Research on preconception care in the context of infertility prevention has expanded steadily. However, Future research should prioritize longitudinal and interventional studies, foster global collaboration, and align with broader reproductive justice goals to strengthen the evidence base. Ultimately, enhancing the visibility and implementation of PCC in both clinical and public health domains will be pivotal in addressing modifiable infertility risks and promoting equitable reproductive outcomes worldwide.